Production management in banana production units, El Oro province - Ecuador - Palomeque, María; Urdaneta, Armando; Meleán, Rosana (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2023)
This research analyzed production management of 74 agricultural production units, belonging to the Coast Banana Farmers Association (ASOAGRIBAL) from El Oro province - Ecuador. Latent variables were specified such as situational analysis, planning and control and support technology in processes. It were added profitability as a key indicator, considering the financial point of view in this type of organization. The research was positivist, quantitative, analytical, non-experimental, with a transectional and field data design. The data collection instrument designed was the questionnaire, applied through the survey technique. Descriptive results indicate that the variables situational analysis (3.56), planning and control processes (3.40) and production technology platform (3.51) obtained statistical means that allowed them to be classified as good, while the mean value of profitability (3.36) classifies it as regular, far from the classification of excellence. The estimated correlations showed that none of the dimensions under study reached levels of excellence. Results of structural equations model analysis showed a high degree of linear association and positive dependence between the four latent variables; that is, they vary jointly with respect to their average. It is necessary to work on the integration of production tasks as a mechanism to achieve higher levels of profitability, which result in the economic-financial well-being of agricultural companies.